Pesticide poisoning in Chitwan, Nepal: a descriptive epidemiological study - Deepak Gyenwali; Abhinav Vaidya; Sundar Tiwari; Prakash Khatiwada; Daya Ram Lamsal; Shrikrishana Giri (BMC, 2017)
Abstract Background Globally, there is a growing concern over pesticides use, which has been linked to self-harm and suicide. However, there is paucity of research on the epidemiology of pesticides poisoning in Nepal. This study is aimed at assessing epidemiological features of pesticides poisoning among hospital-admitted cases in selected hospitals of Chitwan District of Nepal. Methods A hospital-based quantitative study was carried out in four major hospitals of Chitwan District. Information on all pesticides poisoning cases between April 1 and December 31, 2015, was recorded by using a Pesticides Exposure Record (PER) form. Results A total of 439 acute pesticides poisoning cases from 12 districts including Chitwan and adjoining districts attended the hospitals during the 9-month-long study period. A majority of the poisoned subjects deliberately used pesticides (89.5%) for attempted suicide. The total incidence rate was 62.67/100000 population per year. Higher annual incidence rates were found among young adults (111.66/100000 population), women (77.53/100000 population) and individuals from Dalit ethnic groups (98.22/100000 population). Pesticides responsible for poisoning were mostly insecticides (58.0%) and rodenticides (20.8%). The most used chemicals were organophosphates (37.3%) and pyrethroids (36.7%). Of the total cases, 98.6% were hospitalized, with intensive care required for 41.3%. The case fatality rate among admitted cases was 3.8%. Conclusions This study has indicated that young adults, females and socially disadvantaged ethnic groups are at a higher risk of pesticides poisoning. Pesticides are mostly misused intentionally as an easy means for committing suicide. It is recommended that the supply of pesticides be properly regulated to prevent easy accessibility and misuse. A population-based study is warranted to reveal the actual problem of pesticides exposure and intoxication in the community.